Anti-lipolysis-stimulated lipoprotein receptor antibody-drug conjugate to treat triple-negative breast cancer - Zhou, Zhuoxin “Zora”; Ballard, Davis; Varadkar, Tanvi; Zhang, Jiashuai; Du, Zhantao; George, Ashley; Krabacher, Aaron; Yengo, Rachel; Zhou, Lufang; Liu, Xiaoguang “Margaret” (Frontiers in Oncology, 2025)
Triple-negative breast cancer (TNBC), the most aggressive breast cancer subtype (ER-/PR-/HER2-), is characterized by rapid proliferation, high metastatic rate and frequent recurrence. The development of targeted therapies for TNBC, such as antibody-drug conjugates (ADCs), has been limited by the lack of promising cell surface receptors. Our recent findings revealed that lipolysis-stimulated lipoprotein receptor (LSR) is overexpressed in breast cancer patients. The objective of this study was to develop an anti-LSR monoclonal antibody (mAb) and ADC for TNBC treatment. We observed high transcript and surface expression of LSR across various breast cancer subtypes, with over 63% of TNBC patient tissue samples exhibiting elevated expression. A new mAb targeting the extracellular domain of LSR was developed, engineered, and evaluated in vitro and in vivo. The ADC, constructed by conjugating LSR mAb with a cytotoxic agent mertansine (DM1), demonstrated potent anti-TNBC cytotoxicity in three cell lines. In vivo anti-cancer efficacy was evaluated in two TNBC xenografted mouse models, where a 24 mg/kg-body weight dose of LSR mAb-DM1 reduced tumor burden by 85% in one model and prevented tumor regrowth in the second model. Notably, no off-target effects or systemic toxicity were observed in animal models during or after treatment. This study highlights LSR as a promising therapeutic target and the anti-LSR mAb and ADC as potential targeted therapies for TNBC.